D2 plus radical resection combined with perioperative chemotherapy for advanced gastric cancer with pyloric obstruction - Du, Yian; Cheng, Xiangdong; Xu, Zhiyuan; Yang, Litao; Huang, Ling; Wang, Bing; Yu, Pengfei; Dong, Ruizeng (Chinese Journal of Cancer Research; Vol 25, No 4 (August 24, 2013): Chinese Journal of Cancer Research, 2013)
A patient with advanced gastric cancer complicated with pyloric obstruction was treated using D2 + radical resection combined with perioperative chemotherapy, and had satisfying outcomes. The perioperative chemotherapy regimen was Taxol and S1 (tegafur, gimeracil, and oteracil). Three cycles of neoadjuvant chemotherapy were delivered before surgery, and three cycles of adjuvant therapy after surgery. PR was achieved after chemotherapy. D2 + dissection of stations 8p, 12b, 12p, 13 and 14v lymph nodes was performed on September 10, 2012.